Advances in Geophysics Volume 57 - Collectif; Collectif (Elsevier Science, 2016)
Advances in Geophysics, the latest in this critically acclaimed serialized review journal that has published for over 50 years, contains the latest information available in the field. Since 1952, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now in its 57th volume, it contains material still relevant today. It is truly an essential publication for researchers in all fields of geophysics. Volume 57 of Advances in Geophysics consists of three chapters of interest to a broad readership: "Limit Analysis" is reviewed and explained by Leroy and Maillot, who, apart from presenting the theoretical framework, also present their material in a pedagogic way well-suited for teaching; Malehmir et al. present the state-of-the art in high-resolution geophysical imaging of settings prone to natural hazards by explaining and showing a variety of imaging methods in their rich-illustrated contribution; The importance of light snow in relation to understanding weather and climate is presented by Gultepe et al., who highlight the importance of obtaining high-quality measurements and discuss implications for weather and climate simulations. Contains contributions from leading authorities Informs and updates on all the latest developments in the field